The Effect of Crude Oil Prices and Internet on Economic Growth in Timor Leste - Rumbia, Wali Aya; Muthalib, Abd Azis; Adam, Pasrun; Jabani, Asrul; Pasrun, Yuwanda Purnamasari; Muthalib, Dzulfikri Azis (International Journal of Energy Economics and Policy, 2022)
Continuous economic growth improves the welfare and the living standards of the people. However, for a country to experience economic growth, several factors come into play, including resource endowment, economic policies, political stability, and more. This research aimed to examine the effect of crude oil prices and internet on economic growth in Timor Leste. An autoregressive distributed lag model was used to analyze the time series data from 2005-2020. The cointegration test results showed that crude oil prices, internet, and economic growth are cointegrated. Based on the model coefficients, the estimation results revealed crude oil prices and internet have a significant effect on the country's long-term and short-term economic growth. The long-term effect of crude oil prices on economic growth is negative. In every 1% increase of crude oil prices, there is a 10.3% decrease in economic growth. A 1% reduction in crude oil prices leads to a 10.3% economic growth. Furthermore, the long-term effect of the internet has a long-term positive effect on economic growth. Every 1% internet increase, there is a corresponding 27.65% increase in economic growth.